THE INFLUENCE OF FACTORS OF ENVIRONMENTAL EDUCATION ON THE DEVELOPMENT OF ENVIRONMENTAL AWARENESS THROUGH THE TEACHING OF SCIENCE (Heritage, 2023)
Environmental awareness as an integral part of ecological culture, i.e. part of general culture, is subject to the influence of various factors that lead to its development. Therefore, the subject of this research is reflected in determining the dominant factors that lead to the acquisition of ecological knowledge, and therefore to the development of ecological awareness.The presented research was conducted on a sample of 170 fourth-grade pupils from the ​​Kosovo and Metohija area. The obtained data confirm the third research hypothesis, while the other two hypotheses are not confirmed. Life in nature, that is, cooperation with nature, can be significantly statistically predicted based on kindergarten, school, family and peer group as dominant factors influencing the development of environmental awareness. The reflection of the conducted research can be reflected in the attempts of practitioners to "win" the peer group on their side, having knowledge of the impact on the development of environmental awareness.
Keywords: environmental awareness, factors of environmental awareness, environment, school, family, kindergarten, peer group, science teaching